PENGARUH KOMPETENSI DAN KOMPENSASI TERHADAP DISIPLIN PEGAWAI DI REKTORAT UNIVERSITAS TADULAKO - Natsir, Syahir; Miru, Sulaeman; Safi’i, Ahmad (Katalogis, 2018)
This study aims to determine and analyze simultaneous and partial influence of competency and compensation on discipline of officials in The Rectorate Office of Tadulako University. Population consists of 188 officials who were all selected as respondents. Method of study is causal descriptive with multiple linear regressions analysis. The result shows that competency and compensation simultaneously have a positive and significant influence on discipline of official in The Rectorate Office of Tadulako University with Adjusted R-Square value of 0.450 or 45%, which defines the influence of the independent variables on the dependent variable while the remaining is influenced by other variables that are not studied, on F-value of 75.728 with α=0,05 or α<0,05 sig. F=0,000. Partially, competency has a positive and significant influence on discipline of officials in The Rectorate Office of Tadulako University with regression coefficient of 0.183 on sig. T of 0.000 with value α<0,05 with a confidence level of 95%; compensation has a positive and significant influence on discipline of officials in The Rectorate Office of Tadulako University with regression coefficient of 0.312 on sig. T of 0.000 with value α<0,05 with a confidence level of 95%.